1987
DOI: 10.1109/edl.1987.26681
|View full text |Cite
|
Sign up to set email alerts
|

Laser-recrystallized polycrystalline-silicon thin-film transistors with low leakage current and high switching ratio

Abstract: Laser-recrystallized polycrystalline-silicon thin-film transistors (poly-5i TFT's) with offset-gate structures have been fpbricated on quartz substrates. Offset-gate structures make it possible to reduce leakage currents to as low as 5 X A/pm at V, = 10 V, more than two orders of magnitude lower than that in conventional-structure poly-Si TFT's. Optimization of the dopant concentration in offset-gate regions minimizes degradation of drive current, enabling high switching ratios exceeding lo8. Calculations base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It was reported that the leakage current in the poly-Si TFTs is mainly attributed to thermionic field emission due to the trap states in the region between channel and drain [1]. To reduce the leakage current, there have been suggested two approaches; i) hydrogen passivation to reduce the trap state density in the poly-Si layer [2] and ii) formation of lightly doped drain (LDD) structure to optimize the conventional TFT structure by decreasing electric field at the depletion region [3]. In particular, LDD/offset TFT structures typically require processes with additional photo-lithography steps, which can be disadvantageous in term of yield and cost.…”
Section: Fabricationmentioning
confidence: 99%
“…It was reported that the leakage current in the poly-Si TFTs is mainly attributed to thermionic field emission due to the trap states in the region between channel and drain [1]. To reduce the leakage current, there have been suggested two approaches; i) hydrogen passivation to reduce the trap state density in the poly-Si layer [2] and ii) formation of lightly doped drain (LDD) structure to optimize the conventional TFT structure by decreasing electric field at the depletion region [3]. In particular, LDD/offset TFT structures typically require processes with additional photo-lithography steps, which can be disadvantageous in term of yield and cost.…”
Section: Fabricationmentioning
confidence: 99%
“…Various lightly doped drain (LDD) and offset gated structures have been adopted to suppress the leakage currents by reducing electric field near the drain electrode. 6 However, the ON-currents of LDD and offset TFTs are less than those of self-aligned TFTs due to the high series resistance of the offset (LDD) region if it is longer, and also an additional process step is needed to make the LDD region. 7 In this paper, we studied the fabrication of a 2.2-in.…”
Section: Introductionmentioning
confidence: 99%
“…This is a serious problem for pixel switches in AMOLED. Various lightly doped drain (LDD) and offset gated structures have been proposed to suppress the leakage currents by reducing the electric field near drain [5]. However, the ON currents of LDD and offset TFTs are much less than those of coplanar TFT due to the high series resistance of the offset (LDD) region [6].…”
Section: Introductionmentioning
confidence: 99%